Hubungan Pengetahuan dan Sikap Personal Higiene Remaja Putri Saat Menstruasi dengan Kejadian Infeksi Saluran Repoduksi Kecamatan Seram Barat - Herlin Sinay; Ety Dusra; Desy Vralenda Manuputty (Jurnal Anestesi, 2025)
The prevalence of Reproductive Tract Infections (RTIs) in Indonesia remains quite high. This is primarily due to the poor personal hygiene practices of most adolescents. Objective: This study aims to determine the relationship between knowledge and attitudes with personal hygiene behavior during menstruation among adolescent girls in Manipa Hamlet, Piru Village, West Seram District. Methodology: This research employs a quantitative approach with a cross-sectional study design. The sampling technique used is total sampling. Data were collected using a questionnaire measuring knowledge, attitudes, and personal hygiene behavior during menstruation. Data analysis was conducted using univariate and bivariate analysis and statistical analysis using the chi-square test, with a significance level (p-value).